Health benefit assessment of PM2.5 reduction in Pearl River Delta region of China using a model-monitor data fusion approach. (1st March 2019) - Li, Jiabin; Zhu, Yun; Kelly, James T.; Jang, Carey J.; Wang, Shuxiao; Hanna, Adel; Xing, Jia; Lin, Che-Jen; Long, Shicheng; Yu, Lian
Abstract: The Pearl River Delta (PRD), one of the most polluted and populous regions of China, experienced a 28% reduction in fine particulate matter (PM2.5 ) concentration between 2013 (47 μg/m 3 ) and 2015 (34 μg/m 3 ) under a stringent national policy known as the Air Pollution Prevention and Control Action Plan (hereafter Action Plan). In this study, the health and economic benefits associated with PM2.5 reductions in PRD during 2013–2015 were estimated using the Environmental Benefits Mapping and Analysis Program-Community Edition (BenMAP-CE) software. To create reliable gridded PM2.5 surfaces for BenMAP-CE calculations, a data fusion tool which incorporates the accuracy of monitoring data and the spatial coverage of predictions from the Community Multiscale Air Quality (CMAQ) model has been developed. The population-weighted average PM2.5 concentration over PRD was predicted to decline by 24%. PM2.5 -related mortality was estimated to decrease by more than 3800 due to decreases in stroke (48%), ischemic heart disease (IHD) (35%), chronic obstructive pulmonary disease (COPD) (10%), and lung cancer (LC) (7%). A 13% reduction in PM2.5 -related premature deaths from these four causes yielded a large economic benefit of about 1300 million US dollars. Our research suggests that the Action Plan played a major role in reducing emissions and additional measures should be implemented to further reduce PM2.5 pollution and protect public health in the future. Graphical abstract: Image 1 Highlights: An innovative, open-source data fusion tool was developed to create air quality fields for exposure characterization. Over 3800 avoided deaths in Pearl River Delta (PRD), China were estimated between 2013 and 2015 due to PM2.5 reduction. Health benefits varied spatially across PRD and were limited by the flat slope of the IER model at high concentration.